1999
DOI: 10.1063/1.369464
|View full text |Cite
|
Sign up to set email alerts
|

Optical and electron paramagnetic resonance study of light-emitting Si+ ion implanted silicon dioxide layers

Abstract: Thermally grown SiO2 on Si substrates implanted with Si+ ions with a dose of 6×1016 cm−2 were studied by the techniques of photoluminescence, electron paramagnetic resonance (EPR), and low-frequency Raman scattering. Distinct oxygen-vacancy associated defects in SiO2 and nonbridging oxygen hole centers were identified by EPR. The luminescence intensity in the 620 nm range was found to correlate with the number of these defects. The low-frequency Raman scattering technique was used to estimate the average size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…Many authors also observed a red or infrared PL between 1.3 and 1.9 eV after high-temperature annealing of Si-implanted oxides [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. In [27] it was shown, that the observed emission photon energy of Si-implanted oxides could be tuned between 1.4 and 1.8 eV by varying the annealing time in oxygen at 1000 • C. Im et al implanted thermally grown SiO 2 layers with Si at RT and at 400 • C, and found that the implantation at 400 • C increases the intensity of the yellow PL by 50% to 100% [29].…”
Section: Luminescence Of Ion-implanted Sio 2 Layersmentioning
confidence: 99%
“…Many authors also observed a red or infrared PL between 1.3 and 1.9 eV after high-temperature annealing of Si-implanted oxides [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. In [27] it was shown, that the observed emission photon energy of Si-implanted oxides could be tuned between 1.4 and 1.8 eV by varying the annealing time in oxygen at 1000 • C. Im et al implanted thermally grown SiO 2 layers with Si at RT and at 400 • C, and found that the implantation at 400 • C increases the intensity of the yellow PL by 50% to 100% [29].…”
Section: Luminescence Of Ion-implanted Sio 2 Layersmentioning
confidence: 99%
“…So far, many approaches have been proposed to fabricate the nc-Si structures, such as ion-implantation of Si into SiO 2 [13,14], RF cosputtering [15], and plasma enhanced chemical vapor deposition (PECVD) [16,17]. In this paper, the SiO x thin films have been produced by electron beam evaporation (or e-beam evaporation) of SiO in a vacuum chamber.…”
Section: Introductionmentioning
confidence: 99%
“…The ~740-nm photoluminescence band was observed which was believed to be due to the formation of nc-Si with a mean size of ~4 nm. 36 Thanks to many previous experimental 26,27 and theoretical studies 37 , the nc-Si with a diameter of ~4 nm was estimated to have a band gap of ~1.85 eV. The difference between the band gap and the emission energy indicates that the ~740-nm EL band should not originate from the direct band to band transition within the nc-Si.…”
Section: Resultsmentioning
confidence: 99%